A high-entropy alloy showing gigapascal superelastic stress and nearly temperature-independent modulus - Junming Gou; Guoxin Liu; Tianzi Yang; Xiaolian Liu; Yun Pan; Chang Liu; Yu Qian; Yao Liu; Ying Chen; Xuefeng Zhang; Tianyu Ma; Xiaobing Ren (Nature Communications)
Abstract High-performance superelastic materials with a combination of high superelastic stress, large elastic recovery strain, and stable elastic modulus over a wide temperature range are highly desired for a variety of technological applications. Unfortunately, it is difficult to achieve these multi-functionalities simultaneously because most superelastic materials have to encounter the modulus softening effect and the limited superelastic stress, whereas most Elinvar-type materials show small elastic strain limit. Here, we report a (TiZrHf)44Ni25Cu15Co10Nb6 high-entropy alloy that meets all these requirements. This alloy also shows good cyclic stability, thermally-stable capacity for elastic energy storage, high micro-hardness and good corrosion resistance, allowing it to operate stably in hostile environments. We show that its multi-functionalities stem from a natural composite microstructure, containing a highly-distorted matrix phase with strain glass transition and various structural and compositional heterogeneities from micro- to nano-scale. Our findings may provide insight into designing high-entropy alloys with unconventional and technologically-important functional properties.